Environmental diagnosis in Rio Pajeú, Itapetim, Pernambuco: educational contributi-ons to sustainable development - Almeida, Severina Valéria Gonçalves de; Oliveira, Davi Argemiro Henrique Cardoso de; Sousa Rêgo, Veneziano Guedes de; Medeiros, Felipe Silva de; Farias, Soahd Arruda Rached; Lima, Joedla Rodrigues de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
Environmental deterioration threatens biodiversity, natural resources, population well-being and therefore the services that ecosystems can provide. The present study aimed to evaluate the degree of environmental deterioration in stretches of the upper Rio Pajeú in the municipality of Itapetim, Pernambuco suggesting corrective measures to the deteriorated environment. Data collection was carried out through on-site visits and interviews with farmers using the Environmental Diagnostic Questionnaire (Environmental Factor + Priority Factor). The environmental deterioration was 13% due to the ecologically inadequate use of natural resources. The main priorities reported were low productivity, lack of medical and dental care and problems related to water availability. As a general prognosis, it is suggested to encourage public policies aimed at rural associations as a way of inserting appropriate watershed management practices and environmental education actions that aim at the valorization of existing natural resources. It is concluded that there are ecologically in-adequate rural subsistence and urban growth practices that threaten the maintenance of ecosystem services in Itapetim, Pernambuco.